KESALEHAN SIMBOLIK DALAM PENDIDIKAN AGAMA HINDU : ANTARA SPIRITUALITAS DAN PANGGUNG SOSIAL - Ni Luh Arinata Krista Dewi (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to examine the phenomenon of symbolic piety in Hindu Religious Education in the digital era. The research employed a qualitative approach with a descriptive-critical design. Data were collected through observation, interviews, documentation, and literature studies. The findings show that social media has transformed the religiosity of Hindu youth into a more visual and performative form. Religious symbols such as rituals, traditional attire, and religious activities on social media are interpreted not only as expressions of spirituality but also as means of social imaging. This study also found that Hindu Religious Education still tends to be formalistic and ritualistic, thus not fully fostering students’ reflective spirituality. Therefore, strengthening Hindu Religious Education through contextual, reflective, and religious digital literacy approaches is necessary to build authentic and humanistic religiosity in the digital era.